A logical framework (MYGERYFS) for hospital foodservice to prevent malnutrition among geriatric patients in hospitals, Malaysia: protocol for a feasibility study - Omar, Noraida; Shafiee, Shazli Illyani; Nor'hisham, Siti Hazimah; Ibrahim, Zuriati; Jamaluddin, Rosita; Rahamat, Syafiqah; Mohd Yusof, Barakatun Nisak; Minhat, Halimatus Sakdiah; Sallehuddin, Hakimah; Mazlan, Nur Syazwani (JMIR Publications, 2023)
Background: Geriatric malnutrition in hospitals is common and can be affected by many things, including poor satisfaction toward hospital foodservice. Hospital foodservice plays an important role in a patients recovery process by providing adequate nutrients. On top of that, patients foodservice satisfaction can easily be afflicted by the quality of food served and the overall foodservice experience. Furthermore, malnutrition can occur from poor foodservice quality, especially among geriatric patients. Objective: This study aims to assess the effectiveness of the Malaysian Geriatric Patients Hospital Foodservice Protocol (MYGERYFS). Methods: The protocol comprises 3 phases. Phase One is a cross-sectional study that took place at public hospitals with geriatric wards in the Klang Valley. Univariate data from Phase One were analyzed descriptively. Pearson correlation and chi-square were conducted to find factors associated with foodservice satisfaction. Phase Two involves the collaboration of health care professionals in the geriatric field. In Phase Three, a feasibility study will be conducted to determine the feasibility of the MYGERYFS protocol in a hospital among 60 geriatric patients. These patients will be randomized into control and intervention groups, respectively. Intervention care will be done to ensure the safety of the protocol. Results: Data collection for Phase One of the study has been completed. A total of 233 geriatric respondents with the mean age of 71.39 (SD 7.99) years were gathered. Approximately 51.5 (n=120) of the respondents were female, while 48.5 (n=113) were male, with a mean BMI of 24.84 (SD 6.05) kg/m2. Their mean energy and protein intakes were 1006.20 kcal (SD 462.03 kcal) and 42.60 (SD 22.20) grams, respectively. Based on the Mini Nutritional Assessment, older patients who scored 12-14 (normal) were 27.9 (n=65), those who scored 8-11 (at risk) were 54.9 (n=128), and those who scored 0-7, which is the lowest (malnutrition), were 17.2 (n=40) of the study population. Hence, most patients were at risk of malnutrition. Although a majority of the patients claimed to have good foodservice satisfaction 26.2 (n=61), they also experienced at least 3 barriers during mealtimes. It was found that dietary intake and mealtime barriers were significantly associated with the respondents foodservice satisfaction. Data for Phase Two and Phase Three are yet to be collected and analyzed. Conclusions: This study protocol could potentially benefit the hospital foodservice system and aid in improving geriatric nutritional status.